The Analysis of Speaking Teaching Methods in Engineering Student at Politeknik Negeri Semarang - Hella Ayu Setyanida (Universitas PGRI Semarang, 2017)
This study aimed to answer what kind of teaching methods are used by Politeknik Negeri Semarang’s lecturer in teaching speaking and how the lecturer manages the classroom. This research was conducted at Politeknik Negeri Semarang (POLINES) which was located on Jalan Prof. H. Soedarto, S.H., Tembalang Semarang. The research was conducted on April 2018. The research data in this study consists of some sources information speaking teaching method in sixth semester of POLINES in the academic year 2017/2018. In collecting the data, the researcher used interview, classroom observation and documentation. The data triangulation for the study was done by analyzing all of the teaching methods. In this study, the researcher found that the first is the lecturer used two methods that are outdoor class method and task-based language teaching. However, there are some strength and weakness of those methods. The second is the implementation of classroom management. From the research, the researcher finds that many students still are wrong in pronouncing the word and applying the grammar. Besides, the methods are not the standard method. In addition, the students can find any materials and the institution does not use any handouts. In fact, the curriculum that was created does not follow the curriculum based on 'Panduan Penyusunan Kurikulum' published by Kemenristekdikti.